Impact modification of PP/wood composites: A new approach using hybrid fibers - R. Vardai; T. Lummerstorfer; C. Pretschuh; M. Jerabek; M. Gahleitner; B. Pukanszky; K. Renner (eXPRESS Polymer Letters)
The impact resistance of polypropylene (PP)/wood composites was improved either by the traditional approach of adding an elastomer or by the use of poly(ethylene terephthalate) (PET) fibers. Composites were prepared with various elastomer and PET fiber contents at a constant wood content of 20 wt% for all hybrid composites. Interfacial adhesion was improved by the addition of a maleic anhydride modified PP (MAPP). The components were homogenized in a twin-screw compounder and injection molded into standard tensile bars. Properties were characterized by tensile and impact testing, while scanning electron microscopy (SEM) was applied for studying the structure. A combination of acoustic emission measurements (AE) and SEM was used to understand local deformation processes, the results showing that the traditional route of impact modification with elastomers does not work in wood reinforced PP, since the simultaneous fracture of large wood particles and the cavitation of the elastomer result in limited fracture toughness. On the other hand, polymeric fibers (PET) increase the impact resistance of rigid PP homopolymer matrices reinforced with wood fibers, because they initiate new local deformation processes. The concept of using polymeric fibers for the impact modification of rigid PP/wood composites is an efficient way to extend the field of application of such reinforced materials.